2019
DOI: 10.3390/foods8110563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Protein Hydrolysates from Three Edible Insects: Mealworm Larvae, Adult Crickets, and Silkworm Pupae

Abstract: A comparative characterization of proteins from three edible insects—Tenebrio molitor (mealworm) larvae, Gryllus bimaculatus (cricket), and Bombyx mori (silkworm) pupae—was performed in this study. Proteins were extracted from edible insects and their hydrolysates were prepared through enzymatic hydrolysis with commercial enzymes (Flavourzyme: 12%; Alcalase: 3%). Solubility was significantly higher following enzymatic hydrolysis, while foamability was lower compared to those of the protein control. Angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 42 publications
4
68
0
Order By: Relevance
“…In agreement with the paper of Yoon and coworkers (26), protein hydrolysates of T. molitor and G. bimaculatus did not exert any effect on NO release. A total of eight intervention studies on animal models characterized by hypercholesterolemia, diabetes, obesity, and alcoholic liver damage have been published.…”
Section: Antioxidant Activity Of Edible Insects In Cells and Animal Msupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the paper of Yoon and coworkers (26), protein hydrolysates of T. molitor and G. bimaculatus did not exert any effect on NO release. A total of eight intervention studies on animal models characterized by hypercholesterolemia, diabetes, obesity, and alcoholic liver damage have been published.…”
Section: Antioxidant Activity Of Edible Insects In Cells and Animal Msupporting
confidence: 92%
“…Differently from other studies, Dutta et al (18) showed that aqueous extract of Vespa affinis was able to increase the activity of the endogenous antioxidant enzymes catalase (CAT) and glutathione S-transferase (GST) (18). Table 2 summarizes the results obtained on the antioxidant activity of different insects and invertebrates; eight were tested in cellular models (12,13,18,20,(26)(27)(28)(29) and as many in animal models (20,27,(30)(31)(32)(33)(34)(35). For what concerns cellular models, the effects of the water-soluble extract of dung beetles of Onitis sp., mole crickets of Gryllotalpa sp., grasshopper of Caelifera sp.…”
Section: In Vitro Antioxidant Activities Of Edible Insectsmentioning
confidence: 98%
“…Next, the lipids in grounded or homogenized tissues are then extracted with an aqueous solution using tissue hydrolysis with enzymes, alkaline, or acids to improve the extraction efficiency [15][16][17][18][19]. However, using a hydrolysis reaction limits the potential reuse of protein components and regularly results in a bitter taste [20,21]. Moreover, issues have been reported with attempts to scale up the enzymatic hydrolysis method [22].…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 values of the control and the hydrolysates were strongly correlated with the <3 kD fractions (r = 0.987, p < 0.05), which indicates that the peptides in the <3 kD fraction are key contributors to the α-glucosidase inhibitory activity. The α-glucosidase inhibitory activity of PR-treated sample (IC 50 1.38 ± 0.19 mg/mL) was remarkably higher than not only other treatments and the control but also the hydrolysates of sardine muscle (IC 50 48.7 mg/mL), whey protein isolate (IC 50 4.5 mg/mL), and edible insects (IC 50 > 2.0 mg/mL) including mealworm larvae, crickets, and silkworm pupae [38,44,45]. In many studies, AL, FL, and digestive enzymes including pepsin and trypsin are commonly used to obtain bioactive peptides [38,39,45,46].…”
Section: Discussionmentioning
confidence: 90%